Determinants of Gender Inequality in Research Productivity and Career Advancement of Women Academics in Nigerian Universities - J. Ejike, Ifeyinwa; A. Igwe, Anthony; I. Ukpere, Wilfred (Journal of Ecohumanism, 2025)
Gender inequality persists as a challenge in academia, considerably affecting research productivity and career advancement of women academics in Nigerian universities. This study carefully investigates the determinants of gender inequality in research productivity and career advancement among women academics at the University of Nigeria, Nsukka. Adopting a quantitative descriptive approach and a survey research design, a sample of 134 women academics were drawn randomly to investigate the sociocultural and institutional factors contributing to these inequalities. Despite several research on gender inequality in academic research productivity, there is paucity of studies investigating the underlying factors perpetuating these inequalities. Employing descriptive statistics and principal component analysis, the study offers experiential evidence that sociocultural norms, institutional barriers, and systemic biases greatly limit the research productivity and career advancement of women academics. Findings demonstrate that the contributory factors to gender inequality include embedded gendered expectations, workload imbalances, mentorship and lack of access to research funding. These structural constraints produce a "glass ceiling" effect, which hinders women academics from progressing their career. This study illustrates the urgency with which institutional interventions, policy changes, and focused support systems such as work-life balance policies, mentorship programs, and unbiased research funding are needed to enhance research productivity and career advancement of women academics in Nigerian universities. It is vital that these inequalities be addressed to promote a more inclusive and equal academic environment.